An Overview On Social Innovation Research: Guiding Future Studies - Manuela Rösing Agostini; Luciana Marques Vieira; Rosana da Rosa Portella Tondolo; Vilmar Antonio Gonçalves Tondolo (BBR: Brazilian Business Review)
Social innovation research has been increasing over the last decades in many countries and fields of study. This study understands social innovation (SI) as a way to mitigate social problems, resulting in new or improved solution for a specific community. This paper analyzes the research in the field of social innovation in the business management area, understanding its antecedents and trends. Therefore, the main goal of this paper is to propose a framework to guide further research in social innovation. Through a systematic literature review, the paper offers a preliminary framework with sub-themes of interest, possible contexts and actors involved in social innovation initiatives. The antecedents showed that the SI since the first concepts presents issues related to social change and has evolved to understand the relationships between different actors, between institutions and the social context where it is inserted. The trends link the SI to areas such as institutional theory; social movements theory; power and multi-actors perspective.